Determining the characteristics of new generation children of 3-6 years old - Ebru Kılıçarslan; Sümeyye Yıldız; Dilek Bayram (Journal of Infant, Child and Adolescent Health, 2026)
Aim: This study was aimmed to determine the characteristics of the new generation of 3-6 years old children. Method: The study was planned as a descriptive study. The study was conducted between April and July 2023 with parents of 3-6-year-old children living in Türkiye who accessed the online data collection form. The data were collected using the descriptive characteristics form and the New Generation 3-6-Years-Old Children's Characteristics Assessment Form. The data collection forms were sent online from the parents, and the data were collected using the snowball method. Data were evaluated by descriptive analysis (percentage, frequency). Ethics committee permission was obtained to conduct the study. Results: A total of 202 parents participated in the study. Mothers constituted 98% of the parents who participated in the study. The mean age of the mothers was 33.97±4.133, and the mean age of the fathers was 33.75±6.850. The average age of the children in the study was 4.52±1.087, and 57.9% of the children (n=117) were girls. The developmental characteristics of new generation 3-6-year-old children were categorized into three categories: individual, emotional, and social. Conclusion: It is essential to develop and support the existing potential of children who are emotionally sensitive, intuitive, fond of freedom, and quick to recognize and learn the changes that occur around them. The results obtained in this direction will help determine the developmental characteristics of the new generation of 3-6-year-old children and exhibit the appropriate approach.